Not the Classical Ideal : Athens and the Construction of the Other in Greek Art - Cohen, Beth, (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
A vision of reality in which a pre-eminent human type was defined in opposition to non-ideal 'Others' characterized ancient Greece. In democratic Athens the social structure privileged male citizens, and women, resident aliens, and slaves were marginalized. The Persian Wars polarized the opposition of Greeks and Barbarians. This anthology provides the first investigation of the delineation of otherness across a broad spectrum of the imagery of Greek art. An international cast of authors, with methodologies ranging from traditional to avant-garde, examines manifestations of the Other in Late Archaic and Classical Greek representations that particularly interest them. The 17 chapters develop a nuanced picture of the visual criteria that denoted otherness in regard to gender, class, and ethnicity and also reveal the social and political functions of this remarkable Greek imagery. Also available in paperback (ISBN 9789004117129).